Polycentric metropolitan areas in Europe towards a unified proposal of delimitation - Rafael Boix Domenech; Paolo Veneri; Vincent Almenar; Francesc Hernández (European Regional Science Association (ERSA), 2011)
Metropolitan areas concentrate the main share of population, production and consumption in OECD countries. They are likely to be one of the most important units for economic, social and environmental analysis as well as for the development of policy strategies. However, one of the main problems that occur when adopting metropolitan areas as units of analysis and policy in European countries is the absence of widely accepted standards for identifying them. This severe problem hinders comparative research between European countries using metropolitan areas as units of analysis. In this text we defend the necessity of a methodology to identify metropolitan areas in Europe. This methodology should fulfil three requisites: first, to be useful for analysis and planning, which requires to represent in a realistic way economic, social and environmental phenomena; second, to be applicable to all the European countries; and third, to be flexible enough to deal with the existence of different administrative and territorial structures across countries as well as to take into account that many metropolitan areas, particularly the largest ones, are polycentric. The aim of this paper is to identify metropolitan areas in Spain and Italy using similar methodologies and to evaluate their application to other European countries. The results allow comparing the metropolitan realities of these countries as well as providing the metropolitan units that can be used in subsequent comparative researches. Two methodologies are proposed: the Cheshire-GEMACA methodology (FUR) and an iterative version of the USA-MSA algorithm, particularly adapted to deal with polycentric metropolitan areas. Both methods show a good approximation to the metropolitan reality and produce very similar results: 75 FUR and 67 DMA in Spain (75% of total population and employment), and 81 FUR and 86 DMA in Italy (70% of total population and employment).
Keywords: 330